Sticky Wages in a Stochastic DGE Model of the Business Cycle - Michael Gail (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2004)
In this paper a stochastic dynamic general equilibrium (DGE) model with capital accumulation is augmented by sticky wages. Wages are set in a staggered way as in Taylor (1980) implying that the optimal wage will be set for two periods. Prices are also sticky since there are adjustments cost of prices as in Rotemberg (1982). It is confirmed that wage staggering has a higher potential to generate persistent output responses to a money growth shock. Interestingly, adjustment costs of capital contribute strongly to output persistence. If it is not costly to adjust capital there is no output persistence at all. Price adjustment costs can strengthen the effects of money growth shocks on output in the presence of costly capital adjustment.
Keywords: E52; 330; Monetary Policy; New Neoclassical Synthesis; Sticky Wages; Sticky Prices; Persistence; Real Business Cycle; Geldpolitik; Real Business Cycle; Dynamisches Gleichgewicht; Neue Neoklassische Synthese; Lohnrigidität; Preisrigidität; Theorie